Effect of Chlorogenic Acid Supplementation in MPTP-Intoxicated Mouse - Singh, Saumitra S.; Rai, Sachchida N.; Birla, Hareram; Zahra, Walia; Kumar, Gaurav; Gedda, Mallikarjuna R.; Tiwari, Neeraj; Patnaik, Ranjana; Singh, Rakesh K.; Singh, Surya P. (Frontiers in Pharmacology, 2018)
Oxidative stress and neuroinflammation act as the key players of dopaminergic (DA) neuronal degeneration resulting in hindrance of normal ongoing biological processes in the case of Parkinson’s disease (PD). Several studies have shown that on MPTP administration, different behavioural parameters have suggested motor impairment and damage of antioxidant defence. Thus, the need of the hour is some specific biological molecules that can hinder the dopaminergic (DA) neuronal degeneration through their antioxidant and anti-inflammatory activities. With this objective, we have studied a naturally occurring polyphenolic compound, Chlorogenic acid (CGA) for its antioxidant and anti-inflammatory properties in MPTP intoxicated mice. We observed on CGA supplementation, significant reoccurrence of motor coordination and antioxidant defence, which has been in contrast with CGA untreated MPTP mice. Moreover, enhanced expression of TH within the nigrostriatal region in the case of CGA-treated mice has supported its beneficial effect. Activation of glial cells and oxidative stress level were also estimated using inducible nitric oxide synthase (iNOS) and glial fibrillary acidic protein (GFAP) immunoreactivity within Substantia nigra (SN) and striatum of MPTP injected mice. CGA administration has prevented the neuroinflammation in SN by regulating NF-κB expression in MPTP induced group. Also, significant release of certain pro-inflammatory mediator such as TNF-α and IL-1β have been inhibited by CGA with enhanced expression of anti-inflammatory cytokine IL-10. Additionally, decreased GFAP staining within the nigrostriatal region has supported the fact that CGA has significantly helped in attenuation of astrocytes activation. Hence, our study has shown, CGA supplementation demonstrates its therapeutic ability by reducing the oxidative stress and neuroinflammation in MPTP intoxicated mice.